Mainstreaming Functional Positions within Indonesian Bureaucracy: Half-Hearted Commitment to Professionalization? - Antonius Galih Prasetyo (Jurnal Borneo Administrator, 2022)
The Indonesian government has declared bureaucratic simplification as one of its strategic targets. Based on the understanding that a functional (professional) position is the key to increasing the professionalism of civil servants, a massive "bureaucratic functionalization" was carried out by removing two layers of structural (managerial) positions and transforming them into functional (professional) positions. However, this policy of mainstreaming functional positions presents several problems. This study analyses the issues faced while implementing mainstreaming functional positions from the vantage point of professionalism. The significance of this research is to provide a systematization of the problems encountered in the policy of mainstreaming functional positions by outlining key thematic points and formulating ways to overcome these problems. It uses a qualitative method by combining literature study and observation approach. It reveals that the government genuinely displays a half-hearted commitment to professionalizing the bureaucracy. This can be seen from several pieces of evidence: a regulatory framework which discourages superior performance, the neglection of merit aspect during transformation, the discrepancy between the formal tasks and the actual tasks of functional officers, the lack of incentives and facilities, the discrimination against career functional officers, and the persistence of hierarchy through the new guise. As for the solutions for the identified problems, several measures can be taken: revising the regulatory framework, assessing the abilities and interests of employees before the induction as functional officers, utilizing functional officers more optimally, flattening the organizational structure resolutely, and providing competency development continually